Obtención de azúcares reductores por medio de fermentación sólida a partir de cáscaras de piña (2018)
The purpose of this research project is to obtain products with added value such as reducing sugars for the subsequent production of bioethanol, xylitol, lactic acid, among others, from lignocellulosic residues of agroindustrial type, in turn to look for alternatives to conventional methods of obtaining reducing sugars such as chemical hydrolysis and hydrolysis with isolated enzymes in order to reduce costs and avoid the use of corrosive substances such as sulfuric acid and sodium hydroxide used in chemical hydrolysis. Therefore, the feasibility of using solid fermentation to obtain reducing sugars from pineapple peel of the MD2 variety, better known as ""Golden pineapple"" using the fungus Trichoderma ressei, was evaluated.